A Role Set Analysis of Gender Differences in Performance, Affective Relationships, and Career Success of Industrial Middle Managers - Tsui, Anne S.; Gutek, Barbara A. (Academy of Management Journal, 1984)
Results of a field investigation and a follow-up study suggest that pro-male bias may not prevail in middle management. Women managers seem to be promoted faster and are more satisfied in their jobs than their male counterparts. Contextual and demographic variables may account for observed gender differences in performance and attitudinal outcomes.